ISSUES FOR ENSURING ECONOMIC STABILITY OF CHEMICAL INDUSTRY ENTERPRISES USING FOREIGN EXPERIENCE - Kadirov, Abdumalik (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The purpose of the study is ensure the economic stability of chemical industrial enterprises, the article covers the experience of companies of foreign countries and highlights the aspects of use in local chemical industrial enterprises.